Cholesteryl ester transfer protein gene expression during differentiation of human preadipocytes to adipocytes in primary culture - Gauthier, Benoit; Robb, Malcolm; McPherson, Ruth (Atherosclerosis, 1999)
The expression pattern of the CETP gene in relationship to that of LPL, adipsin, PPAR γ, C/EBP α, ADD1/SREBP1 and actin was examined by RT-PCR during differentiation of human fibroblastic preadipocytes to adipocytes in primary culture. Preadipocytes were isolated from subcutaneous fat obtained from healthy female subjects undergoing mammary reduction procedures, and induced to differentiate in culture. Morphologically, adipogenesis was confirmed by the accumulation of lipid droplets in cells. We show that the gene encoding CETP is expressed in preadipocytes and is present throughout differentiation as compared to LPL and adipsin which were detected in the majority of samples by day 2 or 3 of adipogenesis. The transcription factors, PPAR γ, ADD1/SREBP1 and C/EBP α were expressed by day 2, concomitant with the appearance of LPL and adipsin but subsequent to the appearance of CETP. CETP mRNA was not detectable in human skin fibroblasts. These studies demonstrate that CETP expression is induced at an early stage of commitment to the adipocyte lineage and may be activated by transcription factor(s), which are not members of the PPAR, ADD1/SREBP1 or C/EBP families.